Immature paramphistomosis in a sheep herd - Sivajothi, S.; Sudhakara Reddy, B (International Journal of Biological Research, 2014)
Paramphistomosis is one of the important endo parasitic diseases of small ruminants and causes considerable economical loss to the farmers. The present communication reports about the outbreak of immature paramphistomosis in a sheep herd in Y.S.R.District of Andhra Pradesh. The disease is characterized by sub maxillary edema and severe persistent fluid foetid diarrhoea. Gross examination of the fluid faeces revealed presence of the whitish pink colour round bodies and later they identified as immature paramphistomes. Affected sheep were treated with niclosamide @ 100 mg/kg body weight orally once along with supportive therapy. Keywords: Immature Oxyclozanide, Paramphistomosis, Sheep, Y.S.R.District.